Canadian Geoscience: Charting New Territory in the 21st Century: The Geological Association of Canada Presidential Address, GeoCanada 2010, May 10, 2010 - Lebel, Daniel (Geoscience Canada, 2010)
SUMMARY The Geological Association of Canada Presidential Address is traditionally delivered by the outgoing President of the Association at the annual general meeting; in this case, GeoCanada 2010, held in Calgary, Alberta, provided the opportunity for the 2010 address. The objectives of the address, and of this paper, are: To outline the status and trend information and observations on what economic and natural drivers influenced geoscience societies and geoscience careers in Canada over the last 10 years; To anticipate what the future might hold for individual geoscientists and the organizations for whom they work; To encourage more support for geoscience societies from geoscientists and their employers; and To call for a renewal of cooperation between geoscience associations in Canada and abroad.